Analysis of vocalizations of Long-snouted Bat Platalina genovensium Thomas, 1928 (Chiroptera: Phyllostomidae) - Malo de Molina, Juan A. (2011)
This paper presents the first data on vocalizations of the Long-snouted Bat Platalina genovensium. It is also the first published study on ultrasound analysis of any bat from Peru. The recordings of vocalizations were obtained from flying bats while in their roosts. These roosts were found in two locations near the city of Lima. Each echolocation call was composed of FM fast pulses of 1.30 ms of extremely low intensity (-10 to -35 dB one m away from the recording device), in sequences of 12.90 pulses per second, with 28.58 kHz bandwidth in average, discontinuous, average interpulse of 67.56 ms, and an energy peak in 89.21 kHz. The pulses present a harmonic above 190 kHz. Both, Discrete Fourier Transform and Analysis of the Energy Distribution in frequency bands were used to obtain a predictive equation. This equation is able to predict duration call for 70-80 kHz, 90-100 kHz, and 110-120 kHz energy frequency bands. So, if 110-120 kHz frequency band increases 4%, then duration call decreases 0.2 ms, whereas if 70-80 y 90-100 kHz frequency band increases, then duration call also does it in 0.1 ms. This equation can be used to identify and monitor this species. It also allows us to determine how P. genovensium adapts its energy frequency bands in order to avoid overlap between pulse and echoes.